Compassion satisfaction, compassion fatigue, and intention to leave among critical care nurses in private hospitals of the Cape Metropole - Shelton, Jamie Lee (Stellenbosch : Stellenbosch University, 2023)
Thesis (MNur)--Stellenbosch University, 2023.